(untitled) (Al-Academy, 2022)
Time and space are indispensable basics in cinematic art. They contain the characters, their actions and the nature of events, as well as their expressive abilities to express many ideas and information. However, the process of collecting space and time in one term is space-time, and it is one of Einstein’s theoretical propositions, who sees that Time is an added dimension within the place, so the study here differs from the previous one, and this is what the researcher determined in the topic of his research, which was titled (The Dramatic Function of Space-Time Variables in the Narrative Film), Which included the following: The research problem, which crystallized in the following question: What is the dramatic function of the temporal variables and how they appear in the feature film. The objectives of the research: is to reveal the dramatic function of the temporal variables in the feature film. As well as the researcher to highlight the importance of the research and its limits, and conclude the chapter by identifying the most important terms. It also included (the theoretical framework and previous studies), which was divided into two sections that came as follows: The first topic: conceptual space-time and work. The second topic: spacetime in the feature film, and then (research procedures), as the researcher adopted the descriptive analytical approach, based on the indicators of the theoretical framework as a tool for analysis, and then the research sample was chosen intentionally, and finally the researcher analyzed the research sample. The researcher came out with (the results and conclusions) that the researcher reached after analyzing the sample, and finally recommendations and suggestions were presented, and the research concluded with a list of sources, references and supplements, and a summary of the research in English